Gallic acid production with mouldy polyurethane particles obtained from solid state culture of Aspergillus niger GH1 - Mata-Gómez, Marco (2015)
Gallic acid production in a batch bioreactor was evaluated using as catalytic material the mouldy polyurethane solids (MPS) obtained from a solid-state fermentation (SSF) bioprocess carried out for tannase production by Aspergillus niger GH1 on polyurethane foam powder (PUF) with 5 % (v/w) of tannic acid as inducer. Fungal biomass, tannic acid consumption and tannase production were kinetically monitored. SSF was stopped when tannase activity reached its maximum level. Effects of washing with distilled water and drying on the tannase activity of MPS were determined. Better results were obtained with dried and washed MPS retaining 84 % of the tannase activity. Maximum tannase activity produced through SSF after 24 h of incubation was equivalent to 130 U/gS with a specific activity of 36 U/mg. The methylgallate was hydrolysed (45 %) in an easy, cheap and fast bioprocess (30 min). Kinetic parameters of tannase self-immobilized on polyurethane particles were calculated to be 5 mM and 04.1×102 mM/min for K M and V max, respectively. Results demonstrated that the MPS, with tannase activity, can be successfully used for the production of the antioxidant gallic acid from methyl-gallate substrate. Direct use of PMS to produce gallic acid can be advantageous as no previous extraction of enzyme is required, thus reducing production costs.